LvRas and LvRap are both important for WSSV replication in Litopenaeus vannamei. Issue 88 (May 2019) - Tseng, Yi-Ting; Kumar, Ramya; Wang, Han-Ching
Abstract: The white Spot Syndrome Virus (WSSV) is a pathogen that causes huge economic losses in the shrimp-farming industry globally. At the WSSV genome replication stage (12 hpi) in WSSV-infected shrimp hemocytes, activation of the PI3K-Akt-mTOR pathway triggers metabolic changes that resemble the Warburg effect. In shrimp, the upstream regulators of this pathway are still unknown, and in the present study, we isolate, characterize and investigate two candidate factors, i.e. the shrimp Ras GTPase isoforms LvRas and LvRap, both of which are upregulated after WSSV infection. dsRNA silencing experiments show that virus replication is significantly reduced when expression of either of these genes is suppressed. Pretreatment with the Ras inhibitor Salirasib further suggests that LvRas, which is a homolog to a commonly overexpressed human oncoprotein, may be involved in regulating the WSSV-induced Warburg effect. We also show that while both the PI3K-Akt-mTOR and Raf-MEK-ERK pathways are activated by WSSV infection, LvRas appears to be involved only in the regulation of the mTOR pathway. Highlights: Both LvRas and LvRap were isolated and characterized from white shrimp ( Litopenaeus vannamei ). In vivo knockdown by RNA interference suggests that LvRas and LvRap are both is important for WSSV replication. In vivo suppression of LvRas with the inhibitor Salirasib further suggests its involvement in WSSV replication. LvRas activation is critical for the WSSV-induced Warburg effect. LvRas activation activates the PI3K-mTOR pathway, but not the ERK pathway.